What Influence The Employee To Get Satisfaction And Performance : An Analysis Of Motivation, Individual Characteristics And Organizational Commitment - Hamzah, Fadhil (SEIKO : Journal of Management & Business, 2023)
The purpose of this study is to determine the influence of motivation, individual characteristics, and organizational commitment on employee job satisfaction and performance, as well as to identify the variables that have the greatest influence on job satisfaction and performance among Wood Processing Company Employees in Makassar City. Using secondary and primary data, observation, documentation, interviews, and questionnaires were used to obtain information from 161 samples. Model analysis using Structural Equation Modeling (SEM). The results of this study reveal that 1) Motivation, Individual Characteristics, and Organizational Commitment have a significant impact on job satisfaction and staff performance in wood processing industries in Makassar City. However, organizational commitment has no significant impact on employee performance. Employee motivation has a substantial effect on job satisfaction. 4) Personal characteristics have the most influence on employee success.